Estimating regional wealth in Germany: How different are East and West really? - Ann-Kristin Kreutzmann; Philipp Marek; Nicola Salvati; Timo Schmid (Deutsche Bundesbank, 2019)
More than 25 years after German reunification, key economic indicators for households living in eastern German regions are still below the western German levels. This particularly holds for private net wealth, which reaches only about 40% of the western German level. However, a more granular regional perspective may reveal a more diverse picture. Therefore, this study is designed to develop regional wealth indicators for the 16 federal states and for the 96 regional planning regions (Raumordnungsregionen) in Germany based on the second wave of the Panel on Household Finances (PHF) conducted by the Deutsche Bundesbank in 2014. These estimates are derived by means of a modified Fay-Herriot approach (Fay and Herriot, 1979) dealing with a) the skewness of the wealth distribution using a transformation, b) unit and item non-response, especially the multiple imputation used, and c) inconsistencies of the regional estimates with the national direct estimate. The results show that private wealth in all eastern German regions still remains far below the national average. However, the wealthiest planning regions in the east report higher private wealth figures than the western German regions with the lowest private wealth estimates. Although the paper is particularly focused on Germany, the approach proposed is applicable to surveys with a similar data structure.
Keywords: C13; C83; D13; 330; small area estimation; non-response; multiple imputation; private wealth distribution